The Effectiveness of Project-Based Learning on Writing Skill : an experimental research at Junior High School - Nur Hasanah, Nur Hasanah (JEET, Journal of English Education and Technology, 2023)
This study aims to determine whether teaching writing using project-based learning with canva media improved students' writing skills. The result expects to be useful for students to improve their English writing skills and help teachers to be more creative. This research uses pre-experimental in one class pretest and posttest, and the total sample was 25 students' from eight classes. The data were obtained from the writing test. The result shows that project-based learning with canva significantly increased students' writing after treatment. The mean score improved from 41.00 in the pretest to 64.00 in the posttest. The value of paired sample t-test was -12.283. The considerable value (sig. two-tailed) was 0.000, and the value was <0.05. It can be concluded that the study using project-based learning with canva media could enhance the student's writing skills in learning English for junior high school.